Metabolic Syndrome: Clinical and Policy Implications of the New Silent Killer. (July 2017) - Sherling, Dawn Harris; Perumareddi, Parvathi; Hennekens, Charles H.
The United States is experiencing its greatest life expectancy ever. Nonetheless, the general health of the US population is far from at an all-time high. An important contributor to the pandemic of cardiovascular disease is that overweight and obesity are also the major determinants of metabolic syndrome, an all too common and all too serious clinical and public health challenge. Clinicians have traditionally evaluated each of the major risk factors contributing to metabolic syndrome on an individual basis. There is evidence, however, that the risk factors are more than additive. The overlap of these factors in each disease state, resulting in increased atherogenic risks, is worth examining as a broader entity rather than separately. While therapeutic lifestyle changes (TLCs) should be strongly recommended, clinicians should not let the perfect be the enemy of the possible. Evidence-based doses of statins, aspirin and angiotensin-converting enzyme inhibitors, or angiotensin II receptor blockers should be prescribed as adjuncts, not alternatives, to TLCs. In fact, there is cogent evidence that the benefits of these pharmacologic therapies may also be at least additive.